Hidrólisis ácida de cáscaras de vaina de cacao CCN-51.: Optimización del proceso para generación de azúcares reductores - Sanchez Quezada, Johanna Patricia; Soler Herrero, Jaime; Herguido, Javier (Jornada de Jóvenes Investigadores del I3A, 2018)
The hydrolysis reaction of the shell of the cocoa pod has been studied to generate reducing sugars. For its optimization, experiments were carried out modifying the main operating variables: time, temperature, mineral acid concentration and biomass. The highest production obtained was 51.66% of the total hydrolysable material.